Influence of co-creation signals on observers’ co-creation willingness: A self-determination theory perspective - Zhang, Li; Zhu, Na; Wang, Hui (Frontiers in Psychology, 2022)
With the service-dominant logic gradually replacing the traditional commodity-dominant reason, Co-creating value with consumers has become an essential marketing practice for enterprises. As a critical information carrier in enterprise marketing communication, the co-creation signal impacts co-creation observers. Enterprises are now exploring how to effectively release co-creation signals to attract most observers to participate in value creation activities actively. Based on self-determination theory, this study investigates the influence mechanism of co-creation signals on observers’ willingness to co-create and the moderating role of mental simulation through the experimental method. The conclusions are as follows: (a) The co-creation signal has a significant positive effect on the co-creation intention of observers. Self-designed co-creation signals generate more important co-creation intentions than self-produced co-creation signals. (b) Self-determination and its dimensions mediate the relationship between co-creation signals and the observer’s willingness to co-create. (c) Mental simulation moderates the relationship between co-creation signal and self-determination. This study has important theoretical significance in enriching co-creation signals and mental simulation research. It also provides management implications for enterprises to release co-creation signals and optimize co-creation marketing practice effectively.